(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The present study was undertaken to detect and quantify the left over residue of Fenvalerate and Acephate in bean and tomato and comparison between the detected residue levels with Maximum Residue Limit (MRL) set by FAO/WHO. Two supervised field trials (one for Fenvalerate and another for Acephate) were carried out sprayed with the field dose of Fenvalerate (1.0ml/L of water) and Acephate (1.0gm/L of water). Samples were collected at 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 and 15 days after spray. The left over residue of Fenvalerate was detected up to 14 DAS, of which up to 3 DAS the quantities of residue were above MRL (1 ppm) in both the vegetables (bean, tomato). This insecticide remained 0.601-0.035 ppm residue in bean and 0.443-0.014 ppm in tomato which were below MRL at 4 to 14 DAS. The high amount of Acephate was detected for a longer period than Fenvalerate and it was found up to 14 DAS in which MRL values (0.5 ppm) were found above up to 9 DAS with 0.623 ppm in tomato and 0.928 ppm in bean. Samples of 10, 11, 12, 13 and 14 DAS of Acephate contained residues 0.289-0.032 ppm in bean and 0.465-0.029 ppm in tomato which were below MRL. At 15 DAS, no residue was detected. Therefore, bean and tomato can be harvested safely at 4 days after spray for Fenvalerate and 10 days after spray for Acephate. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 284-290